2018
DOI: 10.1007/s10157-018-1543-9
|View full text |Cite
|
Sign up to set email alerts
|

Is low pre-transplant parathyroid hormone a risk marker for cardiovascular disease in long-term follow-up of renal transplant recipients?

Abstract: BackgroundSecondary hyperparathyroidism and altered levels of parathyroid hormone (PTH) are associated with vascular events in chronic kidney disease. After renal transplantation, this association is not clear. Pre-transplant parathyroidectomy (PTX) is common, but post-transplant data are scarce. We aimed to study the effect of PTH at the time of transplantation on risk of post-transplant vascular events in renal transplant recipients with and without pre-transplant PTX.Methods258 patients from two Swedish tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
5
1
1
Order By: Relevance
“…In contrast, Isaksson et al showed that lower PTH levels in the pre-transplant period are associated with a higher risk of cardiovascular events in the post-transplant period [119]. The association of low PTH levels with worse cardiovascular outcomes has already been demonstrated in dialysis patients and this is one of the hypotheses that explains the finding of this study [25][26][27]119]. Another possible explanation is bone disease associated with reduced PTH, usually with low remodeling.…”
Section: -Abnormalities Of Ckd-mbd Biochemical Parameters After Kidne...contrasting
confidence: 52%
See 1 more Smart Citation
“…In contrast, Isaksson et al showed that lower PTH levels in the pre-transplant period are associated with a higher risk of cardiovascular events in the post-transplant period [119]. The association of low PTH levels with worse cardiovascular outcomes has already been demonstrated in dialysis patients and this is one of the hypotheses that explains the finding of this study [25][26][27]119]. Another possible explanation is bone disease associated with reduced PTH, usually with low remodeling.…”
Section: -Abnormalities Of Ckd-mbd Biochemical Parameters After Kidne...contrasting
confidence: 52%
“…Roodnat et al showed that high PTH levels in the pre-kidney transplant period were associated with a higher risk of graft loss [117]. In contrast, Isaksson et al showed that lower PTH levels in the pre-transplant period are associated with a higher risk of cardiovascular events in the post-transplant period [119]. The association of low PTH levels with worse cardiovascular outcomes has already been demonstrated in dialysis patients and this is one of the hypotheses that explains the finding of this study [25][26][27]119].…”
Section: -Abnormalities Of Ckd-mbd Biochemical Parameters After Kidne...mentioning
confidence: 99%
“…Another contributing factor could be that the prolonged survival time among PTX patients, presented in our former study, might increase the risk of having CVE at some point after PTX. In recent years, more attention has been given to the fact that not only high levels of PTH but also very low levels of PTH are associated with increased mortality [34] and CVE [35,36]. One of the common complications of PTX is low levels of PTH after the procedure, so this could partly explain the higher risk of CVE for PTX patients.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hypoparathyroidism following surgical intervention in SHPT varied between 16.6% and 18.1% (36). Low levels of PTH before KT were associated with an increased risk of post-KT vascular events (37). Marked hypoparathyroidism and hypocalcemia related to pre-KT parathyroidectomy might also lead to slow allograft function, and suboptimal allograft function is significantly related to the diffuse hypoperfusion of the glomeruli (38).…”
Section: 2mentioning
confidence: 99%